EFFECT OF SOME INSECTICIDES ON APHID INSECT MYZUS PERSICAE (Sulzer) AND IT’S PREDATORS AND PARASITES - juhina mohammed ali (Mesopotamia Journal of Agriculture)
Present study aimed to determine the effects of three insecticides which were Actara, Match and Nimex on Myzuspersicae (Sulzer)  and on it’s both parasite Aphidiusmatricariae Halidayand predators Coccinellaseptempunctata L. and CoccinellanovemnotataHerbst. Results showed that all three insecticides effected parasitic efficiency, of Aphidiusmatricariaeand Nimex recorded highest mortality rate on Myzuspersicae (Sulzer) which was 98-73. All three used pesticides (Actara, Match and Nimex) affected predatory and parasitic efficiency after direct exposure, while less effects the same pesticides on predator efficiency of both C.septempunctata  and C. novemnotata have been recorded after indirect treatment.